2017
DOI: 10.1590/s0102-053620170308
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of strawberry cultivated under different colors of low tunnel cover

Abstract: Strawberry is a crop of great economic and social importance. Its fruits are appreciated both for their flavor and nutraceutical potential. Some studies confirm that light quality influences plant physiology. Thus, the aim of this study was to investigate if changes in light spectrum, provided by low tunnels, can improve vegetative traits, as well as, production and fruit quality of strawberry. The authors used six tunnel covers (red, yellow, blue, green, transparent and opaque and one control, without cover),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Mackenzie et al (2011) and Wang and Camp (2000) reported that the TSS value decreased as temperatures increased. High temperatures would increase the metabolic activities and reduce the starch content of plant parts as plants use more soluble carbohydrates (fructose, glucose, and sucrose), which account for >65% of TSS in strawberry (Henschel et al, 2017;Wang and Camp, 2000). In the first year, the 2-week temperature averages (high, low, and average) before the date of the TSS test was increasing (Figure 1c,e,g), and the TSS value was decreasing (Figure 1a).…”
Section: Field Total Soluble Solids (Tss)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mackenzie et al (2011) and Wang and Camp (2000) reported that the TSS value decreased as temperatures increased. High temperatures would increase the metabolic activities and reduce the starch content of plant parts as plants use more soluble carbohydrates (fructose, glucose, and sucrose), which account for >65% of TSS in strawberry (Henschel et al, 2017;Wang and Camp, 2000). In the first year, the 2-week temperature averages (high, low, and average) before the date of the TSS test was increasing (Figure 1c,e,g), and the TSS value was decreasing (Figure 1a).…”
Section: Field Total Soluble Solids (Tss)mentioning
confidence: 99%
“…For example, planting dates affect the TSS and ascorbic acid content of fruits because the difference in temperatures during fruiting affected the accumulation of TSS and ascorbic acids (Rahman et al, 2014). The light and temperature also affect the accumulation of TSS in fruits by controlling the biosynthesis of soluble solids and stomatal opening and closure (Henschel et al, 2017). Cultivars and growing systems affect fruit quality as they can change the harvest dynamics of fruits (Voca et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mulching film cultivation technology in arch sheds can preserve heat, moisture, and soil, improving the survival rate and shortening the planting cycle of crops [1][2][3]. At present, the embedded depth of an arch shed pillar depends on the experience of farmers, which can lead to poor wind resistance of the arch shed and is not conducive to the automatic construction of arch sheds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that compared to traditional open bed strawberry production, low tunnels reduce disease incidence, increase the percent marketable yield, and promote greater marketable yields during the shoulder seasons. Greater total yields and/or fewer runners per plant have also been realized (Anderson et al, 2019;Costa et al, 2017;Henschel et al, 2017;Laugale et al, 2017;Lewers et al, 2017;Orde and Sideman, 2021;Petran et al, 2016;Pritts, 2017;Resende et al, 2010;Soliman et al, 2015;Van Sterthem et al, 2017;Weber et al, 2018;Willden et al, 2021).…”
mentioning
confidence: 99%
“…Furthermore, plant exposure to ultraviolet (UV) radiation triggers the production of secondary metabolites involved in a number of important processes and compounds, including protective compounds that absorb potentially damaging UV rays in the epidermal tissue (Caputo et al, 2006;Kakani et al, 2003;Lamnatou and Chemisana, 2013;Mazza et al, 2000;Schreiner et al, 2017) and those that are responsible for the red color of strawberry fruit (Rein and Heinonen, 2004;Yoshioka et al, 2013). Greater anthocyanin, flavonoid, and/or phenolic contents have been reported for strawberry fruit produced under UV-transparent films than UV-blocking films, and UV-transparent conditions have been associated with a faster rate of color development (Henschel et al, 2017;Tsormpatsidis et al, 2011).…”
mentioning
confidence: 99%